2023
DOI: 10.1007/s10988-023-09390-5
|View full text |Cite
|
Sign up to set email alerts
|

Prolegomena to a theory of X-marking

Abstract: The morphological marking that distinguishes conditionals that are called “counterfactual” from those that are not, can also be found in other modal constructions, such as in the expression of wishes and oughts. We propose to call it “X-marking”. In this article, we lay out desiderata for a successful theory of X-marking and make some initial informal observations. Much remains to be done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…A square of necessities marking on their strong necessity modals. This was one of the core findings in von Fintel & Iatridou's (2008) seminal paper on the crosslinguistic encoding of weak necessity, followed up more recently by von Fintel & Iatridou (2023). It can be nicely illustrated by comparing languages as different from each other as Hungarian, Greek, and Spanish:…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…A square of necessities marking on their strong necessity modals. This was one of the core findings in von Fintel & Iatridou's (2008) seminal paper on the crosslinguistic encoding of weak necessity, followed up more recently by von Fintel & Iatridou (2023). It can be nicely illustrated by comparing languages as different from each other as Hungarian, Greek, and Spanish:…”
Section: Introductionmentioning
confidence: 84%
“…Although the nature of this morphological marking may differ from language to language, another major point made by von Fintel and Iatridou is that the same marking often appears on the consequent of so-called counterfactual conditionals, as in ( 9)-( 11), and also on bouletic verbs expressing unattainable desires, as in ( 12)-( 14 be.pres 'I wish s/he was taller than s/he is.' [Spanish, von Fintel & Iatridou 2023: ex.42] This extra marking, which can show up on strong necessity modals, conditionals and desire verbs, was dubbed X-marking by von Fintel & Iatridou (2023). The authors have set a new research agenda aimed at understanding the semantics of X-marking and envisaging a possible common core underlying the combination of X and the roots to which they attach.…”
Section: Introductionmentioning
confidence: 99%
“…As shown elsewhere (Fuentes 2020(Fuentes , 2023 and illustrated below, the interactions match the behaviour of what has been called 'transparent OUGHT/WISH languages' Iatridou 2008, 2023). An OUGHT transparent language expresses weak necessity (as in (11a)) by marking strong necessity (HAVE TO,as in (10a)) with what has been recently referred to as 'X-morphology' (that is, the morphology that appears in what is traditionally known as 'subjunctive' conditionals; see von Fintel and Iatridou (2023)). As the authors have shown, a related pattern can be traced in the bouletic domain (see also Iatridou 2000 for a first approach).…”
Section: Mapudungun -Fu-: the Interactions With Modalsmentioning
confidence: 99%
“…The 'X' terminology was only introduced in the authors' most recent work(von Fintel and Iatridou 2023).…”
mentioning
confidence: 99%
See 1 more Smart Citation